Application of Shepherd Leadership to the Spiritual Growth of Christian Youth in the Digital Age - Roy Imbing; Remegises Danial Yohanis Pandie (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
Writing this article aims to describe the pastor's strategy in educating, fostering and guiding young people to experience spiritual growth. This article refers to the role of pastors in formulating the right strategy to solve the spiritual problems of young people which are slowly declining due to the pace of technology. Where, young people ignore worship and other spiritual activities such as a lack of interest in worship both in public worship, household worship, youth worship, and worship activities on church holidays. The, method used in this research is literature study which refers to references related to the topic raised. In this study, the authors found that pastors have a strategy to apply their leadership to grow the spirituality of youth through Teaching God's Word with contextual topics, Bible study, coaching and guidance through counseling and the use of digital media. The achievement of pastoral leadership in the spiritual growth of young people is seen in terms of their quality of life. The proof of the spiritual growth of young people is that they will be diligent in participating in fellowship services at church and are able to practice the value of the truth of God's Word to their surroundings.